PENGARUH KUALITAS PRODUK DAN PELAYANAN TERHADAP MINAT BELI ULANG MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA TOKO F3 SITUBONDO - Hariyanto, Hariyanto; Arief, Mohammad Yahya; Praja, Yudha (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
The purpose of the study was to determine the effect of product and service quality on repurchase intention through consumer satisfaction as an intervening variable at the F3 Situbondo Store. The sampling technique used in this study is non-probability sampling with purposive sampling technique with the Slovin formula with a tolerable error rate of 10% as many as 98 people. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM) The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that product quality has a positive and significant effect on consumer satisfaction, service has a positive and significant effect on consumer satisfaction, product quality has a positive and significant effect on repurchase interest, service has a negative and insignificant effect on Repurchase intention, consumer satisfaction has a positive and significant effect on repurchase interest, product quality has a positive but not significant effect on repurchase interest through consumer satisfaction, service has a positive and significant effect on repurchase interest through consumer satisfaction